Night mode prohibitory traffic signs detection - Biswas, Rubel; Khan, Arif; Khan, Mumit; Alom, Md. Zahangir (© 2013 Institute of Electrical and Electronics Engineers Inc., 2017)
This conference paper was presented in the2nd International Conference on Informatics, Electronics and Vision, ICIEV 2013; Dhaka; Bangladesh; 17 May 2013 through 18 May 2013 [© 2013 IEEE] The conference paper's definite version is available at: http://dx.doi.org/978-147990397-9